English Speaking Skills of Students at Sariputta College in Shan State of Myanmar - Indavimsa; Pintrymool, Narongchai; Kittipanyo, Phramaha Somchai (วารสารพุทธจิตวิทยา, 2026)
This study investigates the English speaking skills of students at Sariputta College in Muse, Northern Shan State, Myanmar, where English serves as a vital bridge language among a diverse, multilingual student body. The research addressed three primary objectives: evaluating current speaking skills, analyzing proficiency levels, and identifying both the barriers to communication and potential guidelines for improvement. A mixed-methods approach was utilized, incorporating quantitative data from structured questionnaires administered to 75 students and qualitative insights from semi-structured interviews with four experienced English teachers. Quantitative analysis revealed that students possess a moderate level of speaking proficiency (mean score of 2.682), showing relative confidence in basic self-introductions and short conversations. However, significant weaknesses were identified in pronunciation, grammatical accuracy, and vocabulary usage, which scored at low levels. Qualitative findings corroborated these results, with teachers identifying anxiety, fear of criticism, and limited vocabulary as major psychological and linguistic barriers. The study also highlighted the negative impact of traditional teaching methodologies that prioritize reading and writing over real-time oral interaction. Mother tongue interference from tonal languages like Shan and Burmese was further noted as a critical factor in pronunciation challenges. The study concludes that improving oral proficiency requires a transition toward learner-centered, communicative pedagogies. Key recommendations include the integration of speaking-based activities—such as role-plays, debates, and English-speaking clubs—into the curriculum, alongside the creation of a supportive, low-pressure learning environment. These findings provide a roadmap for educators and policymakers to enhance English language acquisition in similar non-native settings across Myanmar.